Syntheses and Swelling Kinetics Study of Gelatin-g-poly(acrylamide-co-2-acrylamido-2-methyl Propane Sulfonic Acid) Superabsorbent Hydrogel with Salt-Sensitivity Properties - Sadeghi, Mohammad; Ghasemi, Nahid (Asian Journal of Chemistry, 2012)
In this paper, we have focused on synthesis and study of swelling kinetics and salt-sensitivity behaviour of a graft copolymer based on gelatin and acrylamide (AAm), 2-acrylamido-2- methyl propane solfonic acid (AMPS). The polymerization reaction was carried out in an aqueous medium and in the presence of ammonium persulfate as an initiator. The graft copolymer structures were confirmed by FTIR spectroscopy gelatin and the graft copolymer as well as solubility characteristics of the products. The morphology of the samples was examined by scanning electron microscopy. The swelling kinetics of the hydrogels with various particle sizes was preliminary investigated as well. The swelling of the hydrogel showed a second order kinetics of swelling in water. In addition, swelling measurements of the synthesized hydrogels in various chloride salt solutions was measured. Results indicated that a swelling-loss with an increase in the ionic strength of the salt solutions.